Iron status and mental disorders: A Mendelian randomization study - Qiu, Jiaqi; Lian, Fuzhi; Fang, Xuexian (Frontiers in Nutrition, 2022)
Background: Mental disorders account for an enormous global burden of disease, and has been associated with disturbed iron metabolism in observational studies. However, such associations are inconsistent and may be attributable to confounding from environmental factors. This study uses a two-sample Mendelian randomization analysis to investigate whether there is any causal effect of systemic iron status on risk of 24 specific mental disorders. Methods: Genetic variants with concordant relations to 4 biomarkers of iron status (serum iron, ferritin, transferrin saturation, and transferrin) were obtained from a genome-wide association study performed by the Genetics of Iron Status consortium. Summary-level data for mental disorders were obtained from the UK Biobank. An inverse-variance weighted (IVW) approach was used for the main analysis, and the simple median, weighted median and MR-Egger methods were used in sensitivity analyses. Results: Genetically predicted serum iron, ferritin, and transferrin saturation were positively associated with depression and psychogenic disorder, and inversely associated with gender identity disorders. A higher transferrin, indicative of lower iron status, was also associated with increased risk of gender identity disorders and decreased risk of psychogenic disorder. Results were broadly consistent when using multiple sensitivity analyses to account for potential genetic pleiotropy. Conclusions: Our findings offer a novel insight into mental health, highlighting a detrimental effect of higher iron status on depression and psychogenic disorder as well as a potential protective role on risk of gender identity disorders. Further studies regarding the underlying mechanisms are warranted for updating preventative strategies.